STUDI KEPUASAN MASYARAKAT TERHADAP LAYANAN VAKSIN COVID 19 DI PUSKESMAS - Siti Mutia Kosassy; Adelse Prima Mulya; Siti Osa Kosassy (Jurnal Public Administration, Business and Rural Development Planning, 2022)
The covid-19 pandemic is a major public problem that must be resolved by the government as its obligation to protect all citizens. Puskesmas as a national health system is a means of providing individual and community health services. This allows the puskesmas to provide vaccine services to all levels of society in Indonesia. The purpose of this study was to determine community satisfaction with vaccination services at the Puskesmas. This research is a quantitative study using a descriptive method, which was carried out from July to September 2021. The population in the study was people who received the first dose of vaccination at the Mandiangin Health Center, Bukittinggi City. The level of patient satisfaction was measured using the servqual method by distributing questionnaires to 89 people participating in the Covid 19 vaccine. Each statement was scored using a Likert scale of 1-4. In this study, the highest community satisfaction scores were produced in each dimension, namely; Appearance of health workers (87.6%), timely implementation of vaccines (78.6%), vaccine complaints handled properly (75.2%), patient confidentiality maintained (89.8%), and vaccine services do not discriminate differentiate community status (94.3%). Puskesmas need to maintain and improve existing achievements. Some things that need to be considered for further improvement include providing detailed information to the public regarding vaccines as a whole so that the public can receive clear and detailed information.